Caesalpinia bonduc (L) Roxb Seed Extract Dosage and Sex Effects on Pathobiological Changes in A Rat Model of Diabetes Mellitus - Sopianti, Densi Selpia; Doewes, Muchsin; Sumandjar, Tatar; Pamungkasari, Eti Poncorini; Dirgahayu, Paramasari; Febrinasari, Ratih Puspita; Nurwati, Ida (Journal of Multidisciplinary Applied Natural Science, 2026)
Caesalpinia bonduc (L) Roxb is a medicinal plant commonly utilized in traditional Indonesian medicine, particularly for the treatment of diabetes mellitus (DM). This study examined the effects of varying doses C. bonduc extract on fasting blood sugar (FBS), malondialdehyde (MDA), tumor necrosis factor-α (TNF-α), transforming growth factor-β (TGF-β), and pancreatic histology in male and female wistar rats with diabetes. The study design included six groups of 18 male and female rats (Wistar strain) each. To develop diabetes, nicotinamide (NA) (110 mg/kg) and streptozotocin (STZ) (45 mg/kg) were supplied, followed by oral administration of C. bonduc extract at dosages of 200, 400, and 600 mg/kg for 21 days. We utilized ELISA to analyze biochemical parameters and employed H&E staining to evaluate histological changes. A factorial design was employed for the statistical analysis to examine the effects of both dosage and sex. This study offers a unique comparative examination of the antidiabetic efficacy of C. bonduc across genders, a dimension seldom explored in experimental diabetes research. The findings indicated that C. bonduc markedly reduced levels of FBS, MDA, TNF-α, and TGF-β (p < 0.05) enhanced the structural integrity of the pancreas. There were no significant differences between males and female (p > 0.05). The dosage and sex influenced MDA and TGF-β. The extract of C. bonduc shown the ability to lower blood sugar, fight free radicals, and reduce inflammation; however, the intensity of these benefits depended on the dosage given. This means that it might assist persons with diabetes minimize oxidative stress and damage to the pancreas.